2011
DOI: 10.1016/j.bbamem.2011.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Study of the inhibition capacity of an 18-mer peptide domain of GBV-C virus on gp41-FP HIV-1 activity

Abstract: The peptide sequence (175-192) RFPFHRCGAGPKLTKDLE (P59) of the E2 envelope protein of GB virus C (GBV-C) has been proved to decrease cellular membrane fusion and interfere with the HIV-1 infectivity in a dose-dependent manner. Based on these previous results, the main objective of this study was to deepen in the physicochemical aspects involved in this interaction. First, we analyzed the surface activity of P59 at the air-water interface as well as its interaction with zwitterionic or negatively charged lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Synthetic peptides of the GBV-C E2 domain have been shown to interact with the HIV-1 fusion protein and to modify its conformation [142]. This indicates a possible alteration of the interaction of HIV-1 fusion protein with the cell membrane decreasing cellular membrane fusion in a dose-dependent manner [143,144]. Furthermore, Mohr et al have found that naturally occurring GBV-C E2 antibodies from HIV-negative individuals and experimentally induced GBV-C E2 antibodies neutralize HIV-1 infection in vitro by inhibit of HIV attachment, but do not inhibiting HIV entry following attachment [145].…”
Section: Gbv-c: Possible Molecular Interactions With Hivmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic peptides of the GBV-C E2 domain have been shown to interact with the HIV-1 fusion protein and to modify its conformation [142]. This indicates a possible alteration of the interaction of HIV-1 fusion protein with the cell membrane decreasing cellular membrane fusion in a dose-dependent manner [143,144]. Furthermore, Mohr et al have found that naturally occurring GBV-C E2 antibodies from HIV-negative individuals and experimentally induced GBV-C E2 antibodies neutralize HIV-1 infection in vitro by inhibit of HIV attachment, but do not inhibiting HIV entry following attachment [145].…”
Section: Gbv-c: Possible Molecular Interactions With Hivmentioning
confidence: 99%
“…(5) Furthermore, secretion of RANTES, MIP-1α and MIP-1β – natural ligands of the other HIV co-receptor CCR5 – is elevated during GBV-C co-infection leading to lower surface expression of CCR5 [131,137]. (6) Direct inhibition of HIV entry by GBV-C E2 protein has been proposed and interaction of GBV-C E2 with the HIV-1 fusion protein has been shown [141144]. (7) Furthermore, GBV-C E2 Abs have been demonstrated to neutralize HIV-1 infection by inhibition of viral attachment [145].…”
Section: Figurementioning
confidence: 99%
“…Our group has been performing in vitro physical and chemical studies with GBV-C peptide sequences that have proven to be effective as potential inhibitors of HIV-1 FP, yielding results on the interaction of the virus with several sequences of interest [8][9][10][11][12]. HIV-1 FP and GBV-C peptides have amphiphilic properties that allow them to undergo self-assembly in aqueous solution to form various nanoscale architectures.…”
Section: Introductionmentioning
confidence: 99%
“…Surface behaviour at the air-water interface [15][16][17], and in peptide-lipid binding assays [11,18,19], leakage assays, fluorescence anisotropy or fluorescence resonance energy transfer studies [20,21] have each been applied to find a correlate between the capacity to inhibit HIV-1 FP in vitro and in vivo during cell-cell fusion inhibition studies [10,15]. In addition, topographical characterisation of model membranes showing the changes caused by HIV-1 FP or GBV-C peptides in various mixtures have been obtained by fluorescence microscopy (FM) and atomic force microscopy (AFM) [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation